(untitled) (Revista Apotheke, 2020)
This text approaches the relation established between painting and technical image in Manuela Siebert’s production, investigating how such association interfered over the elaboration process and visuality of her works. Thus, it takes into account the making of certain paintings from Silhuetas e Fantasmagorias series. In this set of canvas, the artist conferred to the paintings an aspect similar to mechanically-printed image, adopting techniques and materials of design and visual communication’s field to achieve such end. Thereby, Manuela incorporated in her pictorial practice a logic close to the industrial production mode, characterized by division between project and manufacturing. Executed at pre-determined stages, the paintings show outlines and colors which remind the impersonal and standardized images disseminated by mass media.